PELAKSANAAN ADAT MELAHIRKAN MASYARAKAT BUGIS DI DESA PUNGUR KECIL KECAMATAN SUNGAI KAKAP KABUPATEN KUBURAYA - NIM. A1011201221, NADILLA OKTAVIA (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThis research examines the Implementation of Bugis Community Childbirth Customs in Punggur Kecil Village, Sungai Kakap District, Kuburaya Regency, which has experienced a slight shift both in the implementation stage and in the way of thinking of the community. The customary implementation of the birth of the Bugis community is Maccera' Wettang and Makan Dalam Kelambu. This study aims to obtain data and information on the implementation of the indigenous birth of the Bugis community, reveal the factors of the shift in implementation, reveal the consequences for people who do not carry out the custom of giving birth, and the last reveals the efforts made by the Traditional Elders of Punggur Kecil Village to preserve the Birth Customs of the Bugis Community in Pungur Kecil Village Sungai Kakap District Kuburaya Regency. In this study, the author used empirical legal research methods with a population of 250 (two hundred and fifty) housewives and a sample consisting of 25 (twenty-five) housewives of Punggur Kecil Village. Based on the description found, it can be concluded that the results of the research in the Implementation of Childbirth Customs of the Bugis Community in Punggur Kecil Village, Sungai Kakap District, Kuburaya Regency are still being implemented but there is a shift, the factors causing this shift are several factors, namely religious factors, economic factors and modernization factors. The consequence for those who do not carry out this custom of giving birth is that they experience disaster/disaster which is usually in the form of disease, and the efforts made by traditional elders to preserve the custom of giving birth to the Bugis community are by continuing to carry out the custom and disseminating knowledge.Keywords: Custom; Childbirth Customs; Bugis Indigenous People; Pregnant and Childbirth Women. Abstrak Penelitian ini meneliti Pelaksanaan Adat Melahirkan Masyarakat Bugis di Desa Punggur Kecil Kecamatan Sungai Kakap Kabupaten Kuburaya yang telah mengalami sedikit pergeseran baik dari tahap pelaksanaan maupun pada cara berfikir masyarakatnya. Pelaksanaan adat melahirkan masyarakat bugis ialah Maccera